Optimasi Formula dan Uji Antibakteri Terhadap Staphylococcus aureus dan Propionibacterium acne Pada Sediaan Emulgel Kombinasi Minyak Atsiri Cinnamomum Zeylanicum dan Citrus hystrix dengan Desain Faktorial 2^2 - Anggraeni, Amaliyah Dina (Universitas Muhammadiyah Gresik, 2020)
Cinnamon and lime essential oils are known as antibacterial activity. It contains citronellol, geraniol, cinnamaldehyde, and Eugenol. This study aims to determine the concentration of combination Cinnamomum zeylanicum and Citrus hystrix essential oils in emulgel preparations as an antibacterial against Staphylococcus aureus and Propionibacterium acnes. Dosage formulation of emulgel made in various concentrations of combinations of C. Zeylanicum And C. Hystric Essential Oil that 0.5: 2 (FI); 0.5: 4 (FII); 1: 2 (FIII); 1: 4 (FIV) respectively. Further preparation of the emulgel evaluated physical, chemical characteristics, stability during storage, and antibacterial activity. Factorial design 2^2 used to analyze data on the test characteristics of emulgel preparations. The result showed that all formulations have the characteristics of soft, white, and smells of lime and cinnamon. Viscosity, pH, spreadability, freeze-thaw, and real-time temperature stability did not differ significantly. The F3 showed the highest antibacterial activity against Staphylococcus aureus and Propionibacterium acne with a zone of inhibition of 19.10 mm and 19.10 mm, respectively. Variation of C. zeylanicum and C. hystrix essential oils had a significant pH change in the one-month real-time stability test at various temperatures. The antibacterial activity there was no synergistic effect as an antibacterial, which is shown by the absence of interaction between the two active ingredients. Keywords: Cinnamomum zeylanicum, Citrus hystrix, Factorial design, Formulation, Antibacterial